Three new species of Lecithocera Herrich-Shäffer, 1853 (Lepidoptera, Lecithoceridae) from Taiwan, with a check list of the genus in Taiwan - Park, Kyu-Tek (Zootaxa, 2018)
Three new species of Lecithocera Herrich-Shäffer, 1853; L. quadratiella sp. nov., L. nantouensis sp. nov., and L. meishanensis sp. nov., are described from Taiwan. External and genital features of the new species are illustrated. A check list of the known species of Lecithocera in Taiwan is provided.